Charge-transfer in B-site-depleted NdGaO3/SrTiO3 heterostructures - F. Gunkel; C. Lenser; C. Baeumer; F. Borgatti; F. Offi; G. Panaccione; R. Dittmann (APL Materials, 2018)
Cation stoichiometry has been identified as a major key in establishing 2-dimensional electron gases (2DEGs) in oxide heterostructures. Here, we discuss a 2DEG formation scenario in B-site deficient perovskite/perovskite heterostructures, which previously were predicted to show insulating behavior. We elaborate an ionic picture based on oxygen-vacancy-buffered B-site vacancy defects in the polar oxide layer that yields a continuous transition from 2DEG formation to less conducting interfaces to insulating interfaces with increasing B-site deficiency. Experimentally, a corresponding modulation of charge transfer across NdGaO3/SrTiO3 interfaces is inferred using hard x-ray photoelectron spectroscopy analysis and transport experiments. With increasing B-site deficiency, we observe a decrease of the interfacial Ti3+ core level contribution, indicating a reduced charge transfer at the interface. This result is corroborated by temperature-dependent transport measurements, revealing increased low temperature resistance, with a dominant influence of a reduced electron density in the Ga-depleted sample. We consider a redistribution of oxygen vacancies in the B-site deficient polar oxide layer to explain the alleviated interface reconstruction, adding a new perspective on potential built-up in polar-oxide thin films.